Assessing a new hip index as a risk predictor for diabetes mellitus. Issue 4 (17th November 2017) - He, Sen; Zheng, Yi; Chen, Xiaoping
Abstract: Aims/Introduction: Recently, a new anthropometric parameter (a new hip index [HI]) was developed, and the HI shows a U‐shaped relationship to mortality in the USA population. It is well known that there is an inverse relationship between hip circumference (HC) and the risk of diabetes mellitus. Accordingly, the study sought to investigate whether HI could predict future diabetes mellitus, as compared with HC and the waist‐to‐hip ratio (WHR), in a general Chinese population. Materials and Methods: In 2007, we carried out a health examination of 687 participants (mean age 48.1 ± 6.2 years, male 58.1%). Development of diabetes mellitus by the 2007 examination was studied in relation to data from a baseline health examination carried out in 1992. Results: During the follow up, 74 participants were diagnosed with diabetes mellitus. Across the quintiles of baseline HI, the incidence rates of diabetes mellitus were 12.4, 12.4, 9.9, 7.8 and 11.3% in quintile (Q)1, Q2, Q3, Q4 and Q5, respectively ( P = 0.698). With the lowest quintile (Q1) as reference, univariate and multivariate Cox regression analyses showed that HI was not associated with diabetes mellitus. In contrast, HC and WHR could predict future diabetes mellitus. Furthermore, WHR had the best discriminatory power for diabetes mellitus (area under the receiver operating characteristic curve 0.691, 95% confidence interval 0.621–0.761), followed by HC (area under the receiver operating characteristic curve 0.623, 95% confidence interval 0.558–0.689) and HI (area under the receiver operating characteristic curve 0.464, 95% confidence interval 0.396–0.531). Conclusions: Compared with HC and WHR, HI was not an independent risk factor for diabetes mellitus in the Chinese population. More studies are required to delineate the limits of the utility of HI. Abstract : Recently, a new anthropometric parameter (a new hip index, HI) was developed. HI demonstrates a U‐shaped relationship to mortality in the American populations. It is unclear whether HI could predict the future diabetes in the Chinese population. HI could not predict the new onset of DM in the Chinese population. More studies are needed to delineate the limits of HI's utility